Ignacy Krasicki. Wśród pisarzy polskiego oświecenia - Pokrzywniak, Józef Tomasz (Wydawnictwo Naukowe UAM, 2016)
This book, just like the title, consists of two parts of unequal length. The first part is devoted to the writers of the Polish Enlightenment and their presence in the minds of contemporary recipients of culture after the 200 years that have passed since the end of this literary period. This presence is assessed based on school and university textbooks, reading lists for students as well as publishing series. Adam Mickiewicz’s opinion on the writers of the Polish Enlightenment period counterpoints this picture. This national poet’s opinion is particularly important because he was an authority and has had a great influence on Polish culture. The reflections about Krasicki begin with a critical review of studies on his life and work. These studies commenced over 200 years ago with F.K. Dmochowski’s famous Mowa… [Speech…] and they represent various wise and accurate judgements and opinions, which have stood the test of time in spite of persistent stereotypes that are resistant to facts. This state of knowledge provides a good starting point for studies on selected key issues related to the works of Krasicki, who was both a poet and bishop, such as his religiousness and attitude to classicism as well as the meanings and artistic character of his most important literary works, i.e. Myszeida [Mouseiad], Monachomachia [War of the Monks], Bajki [Fables], Satyry [Satires] or comedies.

Książka podejmuje problematykę recepcji pisarzy polskiego oświecenia w ciągu dwustu lat i po dwustu latach, szczególną uwagę skupiając na twórczości Ignacego Krasickiego i próbując na nowo odczytać najważniejsze jego utwory (poematy heroikomiczne, satyry, bajki, wiersze różne, komedie) i najważniejsze problemy jego życia oraz twórczości (np. religijność pisarza). Całość składa się z dwóch części, z których pierwsza zarysowuje ogólny kontekst rozważań podjętych w części kolejnej, przedstawiając środowisko literackie polskiego oświecenia i skłaniając do refleksji nad mechanizmami i zakresem selekcji kulturowej, skalą swoistej aktywności i pasywności zasobów dziedzictwa literackiego, pochodzących z różnych epok. Druga – główna – część zawiera jedenaście inspirujących i rzetelnych rozpraw oraz szkiców poświęconych Krasickiemu.
Ignacy Krasicki: Among the Writers of the Polish Enlightenment
Keywords: Oświecenie; Krasicki; interpretacja